FES-Assisted Walking with Spring Brake Orthosis: Simulation Studies - R. Jailani; M. O. Tokhi; S. C. Gharooni; B. S. K. K. Ibrahim (Applied Bionics and Biomechanics)
This paper presents a simulation of bipedal locomotion to generate stimulation pulses for activating muscles for paraplegic walking with wheel walker using functional electrical stimulation (FES) with spring brake orthosis (SBO). A new methodology for paraplegic gait, based on exploiting natural dynamics of human gait, is introduced. The work is a first effort towards restoring natural like swing phase in paraplegic gait through a new hybrid orthosis, referred to as spring brake orthosis (SBO). This mechanism simplifies the control task and results in smooth motion and more-natural like trajectory produced by the flexion reflex for gait in spinal cord injured subjects. SBO can eliminate reliance on the withdrawal reflex and foot-ground clearance without extra upper body effort. The stored energy in the spring of SBO is used to replace stimulation pulses in knee flexion and reduce total required torque for the paraplegic walking with wheel walker. The study is carried out with a model of humanoid with wheel walker using the Visual Nastran (Vn4D) dynamic simulation software. Stimulated muscle model of quadriceps is developed for knee extension. Fuzzy logic control (FLC) is developed in Matlab/Simulink to regulate the muscle stimulation pulse-width required to drive FES-assisted walking gait and the computed motion is visualised in graphic animation from Vn4D. The simulation results show that SBO can be successfully used with FES for paraplegic walking with wheel walker with all the advantages discussed over the current hybrid orthoses available.